(untitled) (Journal of Renal and Hepatic Disorders, 2021)
Clinicopathological presentation of lupus nephritis (LN) patients varies with different race and ethinicity of the population. Only few studies describe clinicopathological spectrum of LN patients in the Indian population. The aim of this study was to determine the clinicopathological spectrum of LN in the North-East Indian population. This was a retrospective observational study that included patients with LN at a tertiary care center in North-East India from March 2007 to August 2018. Clinical and histopathological data at the time of presentation were collected from hospital records. Renal biopsies were examined by light microscopy and direct immunofluorescence techniques. A total of 340 patients of LN were included in this study. The mean age of presentation was 22.42 ± 4.3 years. The minimum age at presentation was 8 years and 18.8% belonged to the <18 year age group. The present study showed a male:female ratio of 1:8. The majority of patients were of class IV (71.9%). Arthralgia (47.1%) and anemia (60.3%) were the most common presenting symptom and sign, respectively. Immunoglobulin (Ig) G was the most abundant immunoglobulin (positive in 98.47%) and the least positive was IgA (positive in 41.18%). Complement (C) 3 and C1q were positive in all. Full house deposition was found in 59.3% of the biopsies. The rates of hypertension, microscopic hematuria, renal dysfunction, and nephrotic syndrome were 43.5, 59.12, 45.9, and 35.3%, respectively. Patients of LN in the North-East Indian population present at an earlier age with a more severe form of the disease (class IV) at the time of presentation.